Compensation control strategy for the cutting frequency of the cutterbar of a combine harvester. (April 2021) - Yin, Yanxin; Qin, Wuchang; Zhang, Yawei; Chen, Liping; Wen, Jingqian; Zhao, Chunjiang; Meng, Zhijun; Sun, Suhang
Abstract : For grain combine harversters the correlation between cutting frequency and forward speed is typically based on the theoretical matching value of the cutting pattern. However, in reality cutting frequency is affected by cutting resistance which strongly linked to the physical and mechanical characteristics of the crop stems. Consequently, the field cutting frequency is usually lower the standard setting, resulting in the possibility of increasing losses during harvesting. An optimal cutting frequency model was built firstly based on the cutting pattern but the influencing factors on cutting frequency was analysed, and then a relationship model between cutting energy and cutting frequency was built. A regression model of the influence of wheat stem moisture content and cutting section area on cutting frequency was established by wheat stem cutting experiments. Thus, a cutting frequency compensation control strategy was proposed. To verify the effectiveness of the control strategy, field tests were carried out on uniformly growing wheat fields. The results showed that at the forward speeds of 1 m s −1 and 1.5 m s −1, the maximum deviation between the cutting frequency determined by this proposed approach and the optimal cutting frequency were 0.47 Hz and 1.1 Hz, respectively. Comparing performance without this compensation model, the maximum deviation of the cutting frequency without compensation decreased by 28.33% and 24.60%, respectively. The results indicated that with the proposed approach, the maximum deviation between the field cutting frequency and the predicted optimal cutting frequency could be significantly decreased and the cutting performance of the combine harvester could be observably improved. Highlights: Cutting energy model developed with the physical characteristics of wheat stems. Proposed strategy effectively decreases the cutting frequency. Provides a theoretical basis to optimise cutting performance.